(untitled) (Tanzania Medical Journal, 2009)
Background: Prostate cancer (PCA), the primary disease of men over 50 yrs of age is on the increase worldwide. Most PCA grows slowly from overt clinical diseases to the stages that lead to death. The gradual course of PCA development provides the opportunity for intervention. Objective and methodology: The present study therefore determines the levels of trace metals in 80 Nigeria males having different concentrations of serum PSA using atomic absorption spectrophotometer. Results: Subjects with PSA values 5-10nm/ml had significantly raised levels of Zn, Fe, Cd and Mn but significantly reduced level of Se compared with the controls (PSA 0-4nm/ml). Subjects with PSA >10nm/ml had significantly reduced levels of Mn, Mg and Se compared with the controls. Subjects with PSA values 5-10nm/ml had significantly reduced level of Se compared with subjects with PSA >10nm/ml. Conclusion: Only Se was reduced in all subjects with PSA >4nm/ml, therefore the present study is of the opinion that Se intake may reduce the risk and progression of PCA. Tanzania Medical Journal Vol. 23 (2) 2008: pp. 11-13